FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PIJAT OKSITOSIN TERHADAP KELANCARAN PENGELUARAN ASI DI WILAYAH KERJA PUSKESMAS TANJUNGPANDAN TAHUN 2023 - Sari, Silvi Kurnia (Coping: Community of Publishing in Nursing; Vol 11 No 4 (2023): Agustus 2023DO - 10.24843/coping.2023.v11.i04.p13, 2023)
Breast milk (breast milk) is the best source of food for babies aged 0-6 months. Low breast milk production in the first days post partum is one of the obstacles to exclusive breastfeeding. The solution to increasing breast milk production includes applying oxytocin massage to post partum mothers. The aim of this research is to determine the factors related to oxytocin massage which influence the smooth flow of breast milk in the Tanjungpandan Community Health Center Work Area in 2023. This research is quantitative research with a cross sectional method to determine the cause and effect of the relationship between the independent and dependent variables. The independent variables are mother's knowledge, mother's comfort, and husband's support, while the dependent variable is breast milk expenditure. The total sample was 94 people with purposive sampling technique. Data analysis using chi square test with a confidence level of 95% (? = 0,05). The results of statistical tests on the relationship between maternal knowledge of oxytocin massage and breast milk production (p = 0,000), the relationship between maternal comfort regarding oxytocin massage and breast milk production (p = 0,000), and the relationship between husband's support for oxytocin massage and breast milk production (p = 0,000).